2015
DOI: 10.1186/s13613-015-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Failed noninvasive positive-pressure ventilation is associated with an increased risk of intubation-related complications

Abstract: BackgroundNoninvasive positive-pressure ventilation (NIPPV) use has increased in the treatment of patients with respiratory failure. However, despite decreasing the need for intubation in some patients, there are no data regarding the risk of intubation-related complications associated with delayed intubation in adult patients who fail NIPPV. The objective of this study is to evaluate the odds of a composite complication of intubation following failed NIPPV compared to patients intubated primarily in the medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 50 publications
1
49
1
3
Order By: Relevance
“…In agreement with our results, A recent single center study by Mosier et al, [24] had suggested that in patients who fail on NIV and subsequently, ventilated have poorer outcomes.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results, A recent single center study by Mosier et al, [24] had suggested that in patients who fail on NIV and subsequently, ventilated have poorer outcomes.…”
Section: Discussionsupporting
confidence: 94%
“…More recent studies did not confirm those earlier reports of a benefit from early NIV compared with oxygen therapy . NIV failure is more frequent in patients with cancer and is accompanied by a higher rate of intubation‐associated complications and a worse prognosis, whereas early intubation is correlated with a better outcome . Infection as the cause of acute respiratory failure, high respiratory rate under NIV, a longer delay between admission and initiation of NIV, a need for vasopressors or renal replacement therapy, and acute respiratory distress syndrome were identified as independent factors associated with NIV failure .…”
Section: Icu Referral Of Critically Ill Patients With Cancermentioning
confidence: 73%
“…184,185 NIV failure is more frequent in patients with cancer and is accompanied by a higher rate of intubation-associated complications and a worse prognosis, whereas early intubation is correlated with a better outcome. 9,183,[186][187][188][189][190] Infection as the cause of acute respiratory failure, high respiratory rate under NIV, a longer delay between admission and initiation of NIV, a need for vasopressors or renal replacement therapy, and acute respiratory distress syndrome were identified as independent factors associated with NIV failure. 176,183,190 In an analysis by Azoulay et al, patients who received NIV without subsequent invasive mechanical ventilation had a mortality rate of only 15%, whereas patients with late NIV failure had a mortality rate of 93% versus 78% in patients who received first-line invasive ventilation.…”
Section: Respiratory Failurementioning
confidence: 99%
“…Early predictors of NIV failure include higher severity score, older age, ARDS or pneumonia as the aetiology for respiratory failure, or a failure to improve after 1 h of treatment [89]. Although the reasons for a poorer outcome are not completely understood, patients with NIV failure have higher tidal volumes before intubation [71] and develop more complications after intubation [90]. Studies have shown that NIV failure is an independent risk factor for mortality specifically in this population, although careful patient selection seems to reduce this risk [91,92].…”
Section: Recommendationmentioning
confidence: 99%